Imaging of protein synthesis: in vitro and in vivo evaluation of (44)Sc-DOTA-puromycin - Eigner, Sebastian; Vera, Denis R Beckford; Fellner, Marco; Loktionova, Natalia S; Piel, Markus; Lebeda, Ondrej; Rösch, Frank; Roß, Tobias L; Henke, Katerina Eigner (Molecular imaging and biology, 2013)
PURPOSE: The purpose of this study was to investigate whether (44)Sc-labeled puromycin can be utilized for imaging of protein synthesis in vivo. METHODS: For micro-positron emission tomographic (μPET) studies, 20-25 MBq of [(44)Sc]-DOTA-puromycin was administered to tumor-bearing rats, and animals were scanned for 1 h dynamically. Results were further validated by dissecting organs and tissues of the animals after the measurement and in vitro blocking experiments using puromycin or cycloheximide to block protein synthesis. RESULTS: μPET images of tumor-bearing rats showed significant tumor uptake of [(44)Sc]-DOTA-puromycin and a clear-cut tumor visualization. In both blocking experiments, cellular uptake of [(44)Sc]-DOTA-puromycin ([(44)Sc]-DOTA-Pur) could be suppressed by blocking protein synthesis. CONCLUSIONS: We report for the first time successful μPET imaging with (44)Sc obtained from a (44)Ti/(44)Sc generator, as well as noninvasive μPET imaging of ribosomal activity, respectively protein synthesis, with a puromycin-based radiopharmaceutical and the direct correlation between cellular uptake of [(44)Sc]-DOTA-Pur and protein synthesis.
Keywords: Molecular Imaging; Animals; Heterocyclic Compounds, 1-Ring; Rats; Kinetics; skandium; proteosyntéza; Cell Line, Tumor; puromycin; Tissue Distribution; Puromycin; lidé; molekulární zobrazování; Proteins; heterocyklické sloučeniny monocyklické; Scandium; proteiny; Male; tkáňová distribuce; Protein Biosynthesis; krysa rodu Rattus; pozitronová emisní tomografie; zvířata; mužské pohlaví; Positron-Emission Tomography; kinetika; nádorové buněčné linie; Humans